Choosing and Configuring a Stereo Microphone Technique Based on Localisation Curves - Magdalena PLEWA; Piotr KLECZKOWSKI (Archives of Acoustics)
Whenever the recording engineer uses stereo microphone techniques, he/she has to consider a recording angle resulting from the positioning of microphones relative to sound sources, besides other acoustic factors. The recording angle, the width of a captured acoustic scene and the properties of a particular microphone technique are closely related. We propose a decision supporting method, based on the mapping of the actual position of a sound source to its position in the reproduced acoustic scene. This research resulted in a set of localisation curves characterising four most popular stereo microphone techniques. The curves were obtained by two methods: calculation, based on appropriate engineering formulae, and experiment consisting in the recording of sources and estimation of the perceived position in listening tests. The analysis of curves brings several conclusions important in the recording practice.